Efficacy and safety of lesinurad for the treatment of hyperuricemia in gout - Fernando Pérez-Ruiz; Tim Jansen; Anne-Katrin Tausche; Mónica Juárez-Campo; Ravichandra Karra Gurunath; Pascal Richette (BioExcel Publishing Ltd, 2019)
The aim of this review is to present current evidence about the efficacy and safety of lesinurad in combination with xanthine oxidase inhibitors (XOIs) in the treatment of hyperuricemia in patients with gout. Gout is the most common inflammatory form of arthritis. It is caused by an elevated concentration of serum uric acid (UA) that leads to the formation of monosodium urate crystals in joints and different tissues. The goal of therapy is to maintain serum UA levels at <6 mg/dL (0.36 mmol/L), to prevent the formation and deposition of monosodium urate crystals, and to dissolve existing crystals. Lesinurad, a new uricosuric, increases renal urate excretion by selectively inhibiting the renal uric acid transporter 1 (URAT1). Lesinurad is indicated in adults, in combination with a XOI, for the adjunctive treatment of hyperuricemia in patients with gout (with or without tophi) who have not achieved target serum UA levels with an adequate dose of a XOI alone. With the combination strategy, serum UA targets could be reached with the consequence of inhibiting formation of new crystals and promoting dissolution of existing crystals and, therefore, inducing improvement of outcomes such as flares and tophi. The approval of lesinurad was based on data from three pivotal phase III studies (CLEAR 1, CLEAR 2, and CRYSTAL). These clinical studies assessed lesinurad 200 and 400 mg doses. As only lesinurad 200 mg/day dose was finally approved and commercialized, it will be the focus of this paper. In the pivotal clinical trials, the target serum UA level was achieved by significantly more patients in lesinurad 200 mg plus allopurinol group (CLEAR 1 and CLEAR 2 trials) or lesinurad 200 mg plus febuxostat group (CRYSTAL study) compared with patients who received either XOI alone. In these trials, the safety profile of lesinurad 200 mg plus a XOI was comparable to allopurinol or febuxostat alone. Lesinurad, in combination with a XOI, is an effective and safe treatment that covers unmet needs in adults with gout who have not achieved target serum UA levels with a XOI alone.